3D Mesh Simplification. A survey of algorithms and CAD model simplification tests - Arvo, Jukka; Euranto, Antti; Järvenpää, Lauri; Lehtonen, Teijo; Knuutila, Timo (University of Turku, Technology Research Center, 2015)
Simpliﬁcation of highly detailed CAD models is an important step when CAD models are visualized or by other means utilized in augmented reality applications. Without simpliﬁcation, CAD models may cause severe processing and storage is- sues especially in mobile devices. In addition, simpliﬁed models may have other advantages like better visual clarity or improved reliability when used for visual pose tracking. The geometry of CAD models is invariably presented in form of a 3D mesh. In this paper, we survey mesh simpliﬁcation algorithms in general and focus especially to algorithms that can be used to simplify CAD models. We test some commonly known algorithms with real world CAD data and characterize some new CAD related simpliﬁcation algorithms that have not been surveyed in previous mesh simpliﬁcation reviews.